Investigation of thermal stability and flammability of poly(methyl methacrylate) composites by combination of APP with ZrO2, sepiolite or MMT. (February 2016) - Vahabi, H.; Lin, Q.; Vagner, C.; Cochez, M.; Ferriol, M.; Laheurte, P.
Abstract: The thermal degradation and flame retardancy of poly(methyl methacrylate) containing three mineral fillers, with different geometry, MMT: plate-like, sepiolite: fibrilar and zirconium oxide ZrO2 : spherical, in combination with ammonium polyphosphate (APP) were studied. The flame behavior of composites was investigated using pyrolysis-combustion flow calorimeter, cone calorimeter and LOI tests. The results revealed that the composites containing APP and sepiolite present the best fire behavior. A rheological study was performed on composites to establish a relationship between viscosity and flammability. The residues of samples after cone calorimeter test were studied using X-ray diffraction and micro-tomography in order to investigate their chemical composition and also repartition of fillers. A better repartition of sepiolite during combustion could be the origin of the best results obtained for sample containing this filler.